Physiological concentration of protocatechuic acid directly protects vascular endothelial function against inflammation in diabetes through Akt/eNOS pathway - Chook, Chui Yiu Bamboo; Cheung, Yiu Ming; Ma, Ka Ying; Leung, Fung Ping; Zhu, Hanyue; Niu, Qingshan Jason; Wong, Wing Tak; Chen, Zhen-Yu (Frontiers in Nutrition, 2023)
Background: Cardiovascular diseases (CVDs) have been the major cause of mortality in type 2 diabetes. However, new approaches are still warranted since current diabetic medications, which focus mostly on glycemic control, does not effectively lower cardiovascular mortality rate in diabetic patients. Protocatechuic acid (PCA) is a phenolic acid widely distributed in garlic, onion, cauliflower and other plant-based foods. Given the anti-oxidative effects of PCA in vitro, we hypothesized that PCA would also exert direct effects on endothelial function in addition to the systemic effects on vascular health demonstrated by previous studies. Methods and results: Since IL-1β is the major pathological contributor to endothelial dysfunction in diabetes, the anti-inflammatory effects of PCA specific on endothelial cells were further verified by the use of IL-1β-induced inflammation model. Direct incubation of db/db mouse aortas with physiological concentration of PCA significantly ameliorated endothelium-dependent relaxation impairment, as well as reactive oxygen species overproduction mediated by diabetes. In addition to the well-studied anti-oxidative activity, PCA demonstrated strong anti-inflammatory effects by suppressing the pro-inflammatory cytokines MCP1, VCAM1 and ICAM1, as well as increasing the phosphorylation of eNOS and Akt in the inflammatory endothelial cell model induced by the key player in diabetic endothelial dysfunction IL-1β. Upon blocking of Akt phosphorylation, p-eNOS/eNOS remained low and the inhibition of pro-inflammatory cytokines by PCA ceased. Conclusion: PCA exerts protection on vascular endothelial function against inflammation through Akt/eNOS pathway, suggesting daily acquisition of PCA may be encouraged for diabetic patients.